Islamic Economics Seen from the Philosophy of Science and Integration-Interconnection Paradigm - Syafiq Mahmadah Hanafi; Lailatis Syarifah (Global Review of Islamic Economics and Business, 2022)
The dispute over the building of Islamic economics has not yet reached an agreement. Therefore, this article aims to analyze Islamic economics as science based on the philosophy of science and the integration-interconnection paradigm. This paper concludes that Islamic economics has not been methodologically clear enough, and how the concept of methodology works is obscure because there is no clear pattern. However, Muslim economists have almost agreed that Islamic economics is an independent discipline. Therefore, the approach of integration and interconnection is feasible to apply in developing Islamic economics as the established discipline.